Penerapan Aplikasi E-Masjid pada Masjid Al-Muttaqin Lingkungan XI Kelurahan Tegal Sari Mandala III Kecamatan Medan Denai - Putri Harliana; Nenna Irsa Syahputri; Boni Oktaviana; Mochammad Iswan; Mufida Khairani (Universitas Harapan Medan, 2021)
Website is one of technological tools that is widely used to quickly distribute information to the public today. The Al-Muttaqin Mosque Council (BKM) is a division that aims to carry out religious activities in the community. To increase the dissemination of information to the public, the implementation of website technology at BKM Al-Muttaqin can be the right solution. This community service activity develops a website-based application in the form of an e-mosque which is intended to provide a forum and means of information for BKM Al-Muttaqin to disseminate information related to religious activities so that the public can find out the latest news and information regarding BKM Al-Muttaqin activities. In addition, this activity is also a means to share technological insights with BKM Al-Muttaqin.